2021
DOI: 10.1177/0268580921993327
|View full text |Cite
|
Sign up to set email alerts
|

Achieving sustainable development by enhancing the quality of institutions in Saudi Arabia

Abstract: Economic and human development have been central to all of Saudi Arabia’s strategic plans since 1970, yet the country has not managed to achieve a sustainable rate of development. This study analyzes the most significant governmental dimensions in Saudi Arabia’s economic and human development. This research focuses on helping decision-makers to accomplish and sustain the outcomes of the country’s specific development plans (e.g., Vision 2030). The study uses data collected in the Kingdom of Saudi Arabia from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
2
1
Order By: Relevance
“…Therefore, the hypothesis is fully rejected. This contradicts previous empirical findings for Saudi Arabia (e.g., [24,29,39,53]) which found that a lack of either skilled or trained human resources is a major challenge for urban institutions with regards to achieving sustainable urban development.…”
Section: -Employee Performancecontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, the hypothesis is fully rejected. This contradicts previous empirical findings for Saudi Arabia (e.g., [24,29,39,53]) which found that a lack of either skilled or trained human resources is a major challenge for urban institutions with regards to achieving sustainable urban development.…”
Section: -Employee Performancecontrasting
confidence: 99%
“…Factors such as uniformity of action, enhancing motivation, facilitating procedures, coordination of activities, and effective communication, all play an important role in determining the degree of centralization. Recent academic research has concluded that the decision-making process is still centralized in Saudi Arabia [19,53,54]. Therefore, this study suggests the following hypothesis: Hypothesis 1 (H1).…”
Section: Decision-making/centralizationmentioning
confidence: 69%
See 1 more Smart Citation